The Effect of Financial Knowledge, Financial Attitude, and Internal Locus of Control on Students' Responsible Financial Management Behavior in Yogyakarta with Financial Risk Tolerance as a Moderating Variable - Canda, Faula; Kartini, Kartini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The rapid development of financial technology, accompanied by increasingly consumptive lifestyles among university students, has heightened the risk of irresponsible financial management behavior. This study aims to examine the determinants of responsible financial management behavior among university students in Yogyakarta, focusing on financial knowledge, financial attitude, and internal locus of control, with financial risk tolerance as a moderating variable. A quantitative approach was employed using purposive sampling, involving 230 students aged 18–25 years. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results indicate that financial knowledge, financial attitude, and internal locus of control have positive and significant effects on responsible financial management behavior, suggesting that students with higher financial knowledge, positive financial attitudes, and stronger internal control are more likely to manage their finances responsibly. Furthermore, financial risk tolerance significantly moderates and strengthens the relationship between financial attitude and responsible financial management behavior, but does not moderate the relationships involving financial knowledge and internal locus of control. These findings underscore the importance of enhancing financial knowledge, fostering positive financial attitudes, and strengthening internal locus of control to promote responsible financial behavior among university students.